Benefits of Prescribed Flows for Salmon Smolt Survival Enhancement Vary Longitudinally in a Highly Managed River System. (15th July 2016) - Courter, I. I.; Garrison, T. M.; Kock, T. J.; Perry, R. W.; Child, D. B.; Hubble, J. D.
Abstract: The influence of streamflow on survival of emigrating juvenile Pacific salmonids Oncorhynchus spp. (smolts) is a major concern for water managers throughout the northeast Pacific Rim. However, few studies have quantified flow effects on smolt survival, and available information does not indicate a consistent flow–survival relationship within the typical range of flows under management control. In the Yakima Basin, Washington, the potential effects of streamflow alterations on smolt survival have been debated for over 20 years. Using a series of controlled flow releases from upper basin reservoirs and radiotelemetry, we quantified the relationship between flow and yearling Chinook salmon smolt survival in the 208 km reach between Roza Dam and the Yakima River mouth. A multistate mark–recapture model accounted for weekly variation in flow conditions experienced by tagged fish in four discrete river segments. Smolt survival was significantly associated with streamflow in the Roza Reach [river kilometre (rkm) 208–189] and marginally associated with streamflow in the Sunnyside Reach (rkm 169–77). However, smolt survival was not significantly associated with flow in the Naches and Prosser Reaches (rkm 189–169 and rkm 77–3). This discrepancy indicates potential differences in underlying flow‐related survival mechanisms, such as predation or passage impediments. Our results clarify trade‐offs between flow augmentation for fisheries enhancement and other beneficial uses, and our study design provides a framework for resolving uncertainties about streamflow effects on migratory fish survival in other river systems. Copyright © 2016 John Wiley & Sons, Ltd.